Oral vs. Intravenous Dexamethasone in Third Molar Surgery: A Comparative Study - Awais Hussain, Sadia Majeed, Muhammad Hamza Hashim, Sabeen Arjumand, Muhammad Amjad Bari, Sadaf Raffi (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
The surgical removal of impacted third molars is associated with postoperative pain, swelling, andtrismus that adversely affect recovery